2022
DOI: 10.1101/2022.04.24.489294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth and adaptation mechanisms of tumour spheroids with time-dependent oxygen availability

Abstract: Tumours are subject to external environmental variability. However, in vitro tumour spheroid experiments, used to understand cancer progression and develop cancer therapies, have been routinely performed for the past fifty years in constant external environments. Furthermore, spheroids are typically grown in ambient atmospheric oxygen (normoxia), whereas most in vivo tumours exist in hypoxic environments. Therefore, there are clear discrepancies between in vitro and in vivo conditions. We explore these discrep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The presence of FUCCI signals indicate living cells and a large central region that lacks FUCCI signals indicates a necrotic core (Fig 1G). We have previously shown that the seminal Greenspan mathematical model describes monoculture spheroid growth remarkably well [5, 6, 7, 21] (Fig 1E-H). Here, we quantitatively directly connect Greenspan’s model to co-culture spheroid data for the first time.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…The presence of FUCCI signals indicate living cells and a large central region that lacks FUCCI signals indicates a necrotic core (Fig 1G). We have previously shown that the seminal Greenspan mathematical model describes monoculture spheroid growth remarkably well [5, 6, 7, 21] (Fig 1E-H). Here, we quantitatively directly connect Greenspan’s model to co-culture spheroid data for the first time.…”
Section: Introductionmentioning
confidence: 90%
“…At later times proliferation at the periphery balances mass loss from the necrotic core resulting in a limiting spheroid structure [5, 6, 21]. To define R n ( t ) we consider oxygen mechanisms [7]. Oxygen, reported in terms of oxygen partial pressure p ( r, t ) [%], diffuses within the spheroid and is consumed by living cells at constant rate per unit volume of cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations